Bonus incentives and team effort levels: Evidence from the "Field"*. (25th June 2020) - Butler, Robert; Lenten, Liam J. A.; Massey, Patrick
Abstract: This study explores the effect of bonus incentive mechanisms with a focus on how such a scheme influences aggregate production levels of teams of workers, specifically. We identify this using data from a highly competitive setting in professional sport, which involves a unique tournament design rule in an elite European rugby competition. The modelling results demonstrate qualified evidence that introducing bonuses to encourage teams to score via the most‐difficult, highest‐reward mode, incentivizes teams to increase effort to earn the bonus, and without reducing production after the bonus is achieved.